Naming racism in the public health classroom - Abuelezam, Nadia N. (PLoS One, 2020)
OBJECTIVE: The discussion of racism within undergraduate public health classrooms can be highly influenced by local and national conversations about race. We explored the impact of local and national events on students’ ability to name racism on a public health exam highlighting the impact of racism on maternal and infant health disparities for Black mothers. METHODS: We undertook this research within the context of an undergraduate introductory public health course at a primarily white institution in the Northeastern part of the United States. A qualitative content analysis of undergraduate student responses to a final exam question soliciting the importance of racism to health outcomes among Black mothers in the United States was undertaken. ANOVA tests were run to assess differences on naming racism, using semantic alternatives, and providing alternative explanations during three main time periods: prior to the election of the 45th president of the United States (pre-Trump), after the election (post-Trump), and after a nationally recognized racist campus incident. RESULTS: Between the pre- and post-Trump periods we see no differences in naming racism or providing alternative explanations. We do see a reduction in the proportion of students providing semantic alternatives for racism in the post-Trump period (32.2 vs. 25.2%, p = 0.034). After the racist campus incident, we see increases in the proportion of students naming race (53.6 vs. 73.8%, p = 0.021) and decreases in the proportion providing an alternative explanation (43.1 vs. 12.9%, p = 0.004), but no differences in the proportion of students who used semantic alternatives. DISCUSSION: This work lends itself to our understanding of how local climate affects public health teaching and may also influence students’ learning about important social and structural determinants of health. National and local climate should frame and guide public health teaching.